Formation of GeV, SiV, and NV Color Centers in Single Crystal Diamond Needles Grown by Chemical Vapor Deposition. Issue 9 (7th March 2019) - Malykhin, Sergei; Mindarava, Yuliya; Ismagilov, Rinat; Orekhov, Anton; Jelezko, Fedor; Obraztsov, Alexander
Abstract : Herein the color centers formation in diamond crystallites of pyramidal shape grown by chemical vapor deposition (CVD) is described. The individual crystallites are extracted from polycrystalline films grown on silicon substrates. The silicon‐vacancy (SiV), germanium‐vacancy (GeV), and nitrogen‐vacancy (NV) centers are created by introducing corresponding precursors from substrate material, gaseous nitrogen, and thermally evaporated germanium added during CVD. Some amount of NV centers detected in all types of the diamond crystallites is assigned to uncontrollable presence of nitrogen in the CVD reactor. The low temperature photoluminescence spectra indicate presence of ensembles of SiV centers in diamond structure. The SiV centers are concentrated predominantly at apexes of the diamond crystallites located at substrate surface. Intense growth of CN radicals in plasma‐activated gas environment during CVD process is detected after nitrogen gas addition. The crystallites obtained with the nitrogen addition demonstrate significant variation of their pyramid angle. The photoluminescence spectra of crystallites grown with nitrogen addition demonstrate increase of both negatively and neutrally charged states of NV color center. The GeV centers are created via thermal evaporation of pure Ge during CVD growth. The photoluminescence spectra of the crystallites grown with Ge addition demonstrate presence of GeV color centers ensemble. Abstract : Controllable creation of NV, SiV, and GeV color centers in single crystal diamond needles is achieved via suitable precursors introduction into gas mixture during CVD growth. Substrate material, gas addition, and evaporation are used for that purpose. Photoluminescence characteristics of the created color centers are determined at room and low temperatures.